2024
DOI: 10.1001/jamaneurol.2024.0551
|View full text |Cite
|
Sign up to set email alerts
|

Use of Recommended Neurodiagnostic Evaluation Among Patients With Drug-Resistant Epilepsy

Matthew Spotnitz,
Cameron D. Ekanayake,
Anna Ostropolets
et al.

Abstract: ImportanceInterdisciplinary practice parameters recommend that patients with drug-resistant epilepsy (DRE) undergo comprehensive neurodiagnostic evaluation, including presurgical assessment. Reporting from specialized centers suggests long delays to referral and underuse of surgery; however, longitudinal data are limited to characterize neurodiagnostic evaluation among patients with DRE in more diverse US settings and populations.ObjectiveTo examine the rate and factors associated with neurodiagnostic studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Witnessing this can be seriously disheartening and make one feel horrified and distrustful of the pathway to epilepsy surgery, despite its proven efficacy in treating drug-resistant epilepsy. 4 To replenish my spiritual reserves, I turned to my faith, Islam, and recalled a prophetic adage that resonated with the situation. In the books of hadiths, it is reported that the Prophet Mohammed, Peace Be Upon Him, once encountered a woman who was suffering from epilepsy who shared her predicament: "I get attacks of epilepsy and my body becomes uncovered."…”
mentioning
confidence: 99%
“…Witnessing this can be seriously disheartening and make one feel horrified and distrustful of the pathway to epilepsy surgery, despite its proven efficacy in treating drug-resistant epilepsy. 4 To replenish my spiritual reserves, I turned to my faith, Islam, and recalled a prophetic adage that resonated with the situation. In the books of hadiths, it is reported that the Prophet Mohammed, Peace Be Upon Him, once encountered a woman who was suffering from epilepsy who shared her predicament: "I get attacks of epilepsy and my body becomes uncovered."…”
mentioning
confidence: 99%